Critical Criteria for Diagnosing Anaphylaxis - Brown,SGA; Turner,PJ (2017)
Anaphylaxis is a severe, immediate-type generalized hypersensitivity reaction affecting multiple organ systems and characterized at its most severe by bronchospasm, upper airway angioedema, hypotension and collapse. Lifetime prevalence is estimated to be 0.05–2%, but while anaphylaxis can be life-threatening, fatal anaphylaxis is rare. Drugs, foods and insect stings are the commonest triggers. The cornerstones of emergency management are support of the airway and/or ventilation, a supine position, epinephrine, and volume expansion. In the community setting, early administration of rescue epinephrine and contact with Emergency Services are of equal importance. Following an episode of anaphylaxis, prevention of further episodes requires identification of likely trigger(s) and co-factors, optimizing the management of comorbidities, allergen avoidance strategies, and immunotherapy if available. Patient education including an Anaphylaxis Action Plan and an epinephrine auto-injector should be considered where an allergen may be encountered unexpectedly (food and insect sting anaphylaxis, idiopathic anaphylaxis).